Recent Advances in Imprinting Disorders. Issue 1 (4th August 2016) - Soellner, L.; Begemann, M.; Mackay, D.J.G.; Grønskov, K.; Tümer, Z.; Maher, E.R.; Temple, I.K.; Monk, D.; Riccio, A.; Linglart, A.; Netchine, I.; Eggermann, T.
Abstract : Imprinting disorders (ImpDis) are a group of currently 12 congenital diseases with common underlying (epi)genetic etiologies and overlapping clinical features affecting growth, development and metabolism. In the last years it has emerged that ImpDis are characterized by the same types of mutations and epimutations, i.e. uniparental disomies, copy number variations, epimutations, and point mutations. Each ImpDis is associated with a specific imprinted locus, but the same imprinted region can be involved in different ImpDis. Additionally, even the same aberrant methylation patterns are observed in different phenotypes. As some ImpDis share clinical features, clinical diagnosis is difficult in some cases. The advances in molecular and clinical diagnosis of ImpDis help to circumvent these issues, and they are accompanied by an increasing understanding of the pathomechanism behind them. As these mechanisms have important roles for the etiology of other common conditions, the results in ImpDis research have a wider effect beyond the borders of ImpDis. For patients and their families, the growing knowledge contributes to a more directed genetic counseling of the families and personalized therapeutic approaches. Abstract :